Evaluación del marco normativo urbano del Área Metropolitana de Monterrey - García Ortega, Roberto (El Colegio de México A.C., 1999)
Since the 1980s, the Metropolitan Area of Monterrey (MAM), like other Mexican cities, has stockpiled an arsenal of urban norms, concerning both legal issues and urban planning, regulations and management. Nevertheless, the successes achieved on paper often contrast with the reality of urban space. In several cases, laws, plans, regulations or urban development plans would seem to have been passed as an end in themselves. It is almost as though the goal were to fulfill a politic-administrative requirement, rather than to achieve the aims of urban order and social justice that should be achieved through the fulfillment and implementation of these instruments. This article seeks to identify MAM's particular flaws. At the same time, as happened in the rest of the country, the current instruments comprising MAM's normative framework lack follow-up and evaluation mechanisms. Consequently, this article, which is part of a broader research project, begins with the exposition of and possible answers to certain doubts raised by the attempts to evaluate Monterrey's current metropolitan normative framework. In this respect, the main contribution of this article is its analysis of the sixty questionnaire-interviews conducted among key local informants, all important social actors linked to the legal, normative, management and social participation background to the plans and programs concerning MAM's urban development in recent years. The central aim of this article is to generate a number of conclusions and proposals that seek to improve MAM's current urban normative framework and achieve a more socially equitable distribution of the burdens and benefits of metropolitan urban development.